Sibolga Coastal Dance as Sumut Local Content in Learning Art Culture - Sitti Rahmah; Yusnizar Yusnizar; Raden Raden (Budapest International Research and Critics University, 2021)
The diverse arts and culture of North Sumatra with distinctive characteristics is a potential that can be introduced through education in schools. Cultural arts can contribute to students having an attitude of pride towards their own nation's culture which can be felt with an aesthetic experience in working through learning at school. Learning arts and culture aims to develop aesthetic and artistic sensitivity, critical, appreciative, and creative attitude in students as a whole. This study aims to raise the potential of North Sumatran culture, especially the Sibolga Coastal Dance which can be implemented in learning cultural arts in schools as local content. The problem in this study arises from the lack of local content in North Sumatra which can be used as a learning resource in schools in the hope that students' knowledge of the richness of North Sumatran traditional arts will increase. This research produces a textbook product about the Sibolga Coastal dance that can assist teachers in carrying out their duties as well as a form of optimizing teacher competence in learning. The content of the material in text and context explores the local wisdom of North Sumatra, especially discussing dance from the Sibolga Coast, and will be guided by the 2013 curriculum, especially class X at the high school level.